(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
A speciation study of Al, Cd, Cu, Mn, Pb and Zn in soil samples from a metal recycling factory in Ile-Ife Osun State, Nigeria, was carried out in order to assess the heavy metal pollution impact of the industrial processes on the immediate environment. Surface soil dust samples collected within the vicinity of the factory were subjected to a five-stage sequential extraction process. Levels of heavy metals in each fraction were determined using Flame Atomic Absorption SpectrophotometerÂ (FAAS). The overall mean values obtained for the metals in the fractions gave the range: Al (0.03 Â± 0.01 to 0.20 Â± 0.01 Âµg/g ); Cd (0.03 Â± 0.01 to 0.23 Â± 0.02 Âµg/g) ; Cu (2.93 Â± 0.02 to 18.30 Â± 1.95 Âµg/g) ; Mn (17.33 Â± 0.03 to 91.68 Â± 2.90 Âµg/g); Pb (0.03 Â± 0.01 to 0.43 Â± 0.02 Âµg/g)Â and Zn (8.20 Â± 0.01 to 35.08Â Â±Â 0.02Â Âµg/g) . Both the contamination index and enrichment factor results indicated that all the soil samples were contaminated with Cd while a few sites showed Cu contamination. The mobility potential of the metals in the soil sample decreased in the order: Mn > Al > Zn > Cd > Cu > Pb (West) and Cd > Al > Pb > Zn > Mn > Cu (East). The study revealed that the soil around the metal recycling factory is contaminated with heavy metals, and if left unmonitored and controlled could lead to serious environmental risk in the future.Â